PERANCANGAN BUKU KREASI “LIMBAH TUTUP BOTOL SEBAGAI MEDIA INSPIRATIF” - Ade Widia Safitri; Mukhsin Patriansyah; Husni Mubarat (Besaung : Jurnal Seni Desain dan Budaya, 2016)
The Remaining Waste Is Material Exiles Its Not Used Longer From The Findings One Activities Happens In 'Society. Waste Plastic Bottle Caps And Metal It's Difficult To Review Outlined Should Be Hundreds And Even Thousands Year To Review The Waste Make Really Unravel. Plenty Less Society To Know How To Use And Manage The Goods Subject To The Cap Being Helpful. By Therefore, Book Creations Singer Waste Bottle Caps Designed To Review Gives Inspiration Shown To 'The Public For Review Can Cultivate Well As Utilizing Waste Plastic Bottle Caps And Metal Being Helpful Goods Subject. Keywords: Books, Creative, Waste, Bottle Caps, Knowledge